EXPLORING STUDENT’S IN LEARNING ENGLISH SPEAKING THROUGH ENGLISH CLUBACTIVITIES AT SMP NEGERI 9 SALATIGA - Nadaa Nailussa’dah; Bismi Khairul Rizal; Jendra Syuja Lukmana (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2026)
This study explores how fun English Club activities can help improve students’ speaking skills at SMP Negeri 9 Salatiga. Many junior high school students feel shy, nervous, or afraid of making mistakes when speaking English in class. English Club provides a relaxed and enjoyable environment where students can practice speaking without pressure. Using a descriptive qualitative design, data were collected through observations, questionnaires, and interviews with eight English Club members. The findings show that students enjoy the club because the activities are fun, varied, and help them practice vocabulary, pronunciation, and fluency. They also feel more confident to speak English because their friends and tutors give positive support. However, some challenges still appear, such as noise, discipline problems, and limited vocabulary. Overall, the study concludes that English Club can be an effective way to enhance students’ speaking skills when activities are enjoyable, supportive, and well-organized. The study also highlights the need for better classroom management and consistent practice to help students overcome remaining difficulties.